Violência entre parceiros íntimos e álcool: prevalência e fatores associados - de Oliveira, Janaina Barbosa [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Simao, Maria Odete [UNESP]; Cavariani, Mariana Braga; Tucci, Adriana Marcassa; Kerr-Corrêa, Florence [UNESP] (Pan Amer Health Organization, 2009)
Objective. To estimate physical violence between intimate partners and to examine the association between violence and sociodemographic variables, use of alcohol, and other related factors.Method. This epidemiologic survey included a stratified probabilistic sample representative of the population from the city of São Paulo in economic and educational terms. The Gender, Alcohol and Culture: An International Study (GENACIS) questionnaire was employed. The sampling unit was the home, where all individuals older than 18 years were candidates for interview. The final sample included 1 631 people. Statistical analysis employed the Rao Scott test and logistic regression.Results. The response rate was 74.5%. Most participants were female (58.8%), younger than 40 years of age (52%), or had 5 to 12 years of schooling. of the overall group, 5.4% reported having been victims of physical violence by an intimate partner and 5.4% declared having been aggressors of intimate partners in the past 2 years. Most men declared that none of those involved had ingested alcohol at the moment of aggression. Most women reported that nobody or only the man had drunk. Being a victim or an aggressor was associated with younger age and having a heavy-drinking partner. Women suffered more serious aggression, requiring medical care, and expressed more anger and disgust at aggression than men.Conclusions. The results underscore the importance of the association between alcohol use and risk of aggression between intimate partners, and may contribute to the design of public policies aimed to control this situation.
Violence between intimate partners and alcohol use: prevalence and associated factors
Keywords: Domestic violence; alcohol drinking; epidemiology; Brazil